Trend in cesarean delivery rate among twin pregnancies over a 20 years epoch and the accompanied maternal and perinatal outcomes - Alon Tal; Noah Zafran; Hadar Peretz; Gali Garmi; Shabtai Romano; Raed Salim (Elsevier, 2019)
Objective: To examine the trend of cesarean delivery (CD) rate among twin pregnancies and the trend in maternal and neonatal morbidities within two decades. Study design: Population-based cohort study, conducted at a single teaching hospital in Israel on data between January 1995 and December 2015. All pregnant women with twin gestation who delivered at a gestational age of 24 weeks or more were included. Data on mode of deliveries, Apgar score <7 at 5 min, cord artery pH < 7.1, early postpartum hemorrhage, blood transfusion, and intrapartum fever for each year were extracted and plotted, and trends were analyzed. CDs performed for one or both twins were divided to laboring, i.e., after a trial of labor, and non-laboring CDs. Data was obtained from the hospital discharge register with ICD-9 codes and crosschecked with the labor medical records. The Cochran-Armitage Trend Test was used to identify trends and correlations. Results: Of all 88,145 deliveries that took place during this period, 1955 (2.2%) were twins. Of these 53 were ineligible and were excluded. There was a statistically significant trend (increase) in twins birth over time (p = 0.004). CD rate increased significantly from 43.4% in 1995 to 66.0% in 2015 (p = 0.001). This increase was observed only among non-laboring cesareans (p = 0.001). Multivariate logistic regression analysis revealed that maternal and early neonatal morbidities examined did not differ significantly during the study period. Conclusion: Non-laboring CD rate increased significantly over the past two decades among twin pregnancies. Despite this increase, maternal and early neonatal morbidities did not change. Keywords: Cesarean delivery rate, Maternal morbidity, Neonatal morbidity, Trend, Twin pregnancies